Optimizing the Function of Prosecutorial Intelligence in Law Enforcement - Ismanto Ismanto; Suprapto Suprapto; Nurunnisa Nurunnisa (International Journal of Sociology and Law, 2025)
The function of Prosecutorial Intelligence (Intel Kejaksaan) holds a crucial strategic role, not only in supporting prosecution duties but also in crime prevention, safeguarding national development, and recovering state assets. Despite having a strong legal basis and a broad mandate, this function often faces operational challenges, data integration issues, and resource optimization constraints that limit its effectiveness within the dynamic law enforcement ecosystem. This research aims to deeply analyze the role and challenges of Prosecutorial Intelligence and formulate a model for optimizing its function to enhance the effectiveness of law enforcement in Indonesia. The research methodology employed is normative and sociological juridical with a qualitative approach, gathering data through literature review, regulatory study, and in-depth interviews with practitioners and academics. The findings indicate that the optimization of the Prosecutorial Intelligence function requires three main pillars: (1) Enhancing the capacity and professionalism of human resources (HR) through modern intelligence training and digital forensics. (2) Integrating and ensuring interoperability of the intelligence information system with other law enforcement agencies (Police, KPK, PPATK) to build a comprehensive intelligence big data. (3) Expanding the spectrum of intelligence operations, shifting from a traditional focus on corruption crimes to transnational crimes, cybercrime, and securing strategic national investments. This optimization is expected to transform Prosecutorial Intelligence into a proactive, data-oriented strategic early warning system capable of supporting Prosecutors in making evidence-based decisions, thus achieving effective, just, and impactful law enforcement for the community.